2022
DOI: 10.1111/eci.13757
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum diamine oxidase activity in nonallergic patients with migraine

Abstract: Background/objectives Histamine has shown a possible role in the etiopathogenesis of migraine. It has been reported an association between some polymorphisms in the diamine oxidase (DAO) gene and migraine, especially in women. Two studies addressing DAO activity in migraine patients showed conflicting results. We investigated the possible relationship of serum DAO activity and histamine levels and 3 polymorphisms in the DAO gene with the risk for migraine. Methods We studied the frequencies of DAO rs10156191, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…In another study conducted in Spain with 197 patients with migraine and 245 healthy controls, AOC1 SNP rs10156191, which is linked to decreased DAO enzyme activity, was found to be associated with the risk of developing migraine, especially in women [ 23 ]. In a more recent study, serum DAO activity was found to be increased in patients with migraine, whereas the serum histamine levels were normal, and the polymorphisms were not associated with the risk for migraine as serum DAO activity was assessed [ 24 ]. Histamine has also been implicated in the pathogenesis of migraine.…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted in Spain with 197 patients with migraine and 245 healthy controls, AOC1 SNP rs10156191, which is linked to decreased DAO enzyme activity, was found to be associated with the risk of developing migraine, especially in women [ 23 ]. In a more recent study, serum DAO activity was found to be increased in patients with migraine, whereas the serum histamine levels were normal, and the polymorphisms were not associated with the risk for migraine as serum DAO activity was assessed [ 24 ]. Histamine has also been implicated in the pathogenesis of migraine.…”
Section: Discussionmentioning
confidence: 99%
“… Finding of microglial and parameningeal inflammatory activity in MWA, but not in MWoA, in neuroimaging studies [ 21 ]. Clinical–epidemiological, biochemical, experimental, and pharmacological data give support to the hypothesis of a possible contribution of histamine and mast cells in the etiopathogenesis or the clinical presentation of migraine [ 22 , 23 , 24 , 25 , 26 , 27 ]. Description of alterations in some microRNAs (miRNAs, important regulators to control inflammation), mainly miR-590-5p in migraine patients and animal models of migraine [ 28 ].…”
Section: Discussionmentioning
confidence: 88%
“…Clinical–epidemiological, biochemical, experimental, and pharmacological data give support to the hypothesis of a possible contribution of histamine and mast cells in the etiopathogenesis or the clinical presentation of migraine [ 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 88%
“…(García-Martín et al 2015). Though, in a more recent study, serum DAO activity was increased in patients with migraine, but serum histamine levels were normal, and the polymorphisms was not associated with the risk for migraine considering that was analyzed in serum DAO activity (García-Martín et al 2022). Also, histamine has been implicated in the pathogenesis of migraine: a study investigating the possible association between functional single nucleotide polymorphisms in the diamine oxidase gene in the chromosome 7q36.1 with the risk for migraine reported lack of association between Thr105Ile SNP (rs1801105) polymorphism in the HNMT gene located at chromosome 2q22.1 (García-Martín et al 2007).…”
Section: Discussionmentioning
confidence: 93%